(untitled) (Journal of Laboratory Animal Science, 2022)
Calcium forms the important mineral component of the living system and any alterations in the calcium level may predispose to variety of conditions. Therefore, proper level of calcium in body is thus to be maintained. Being important mineral composition of the body, the various aspects of calcium has been characterized. Relatively, low irritation unlike other nanomaterials, calcium has now been used in nanotechnology. Literature with respect to immunotoxic and cytotoxic effect of calcium nanoparticles is not much cited. However, nanoparticles are known for their smaller size and higher reactivity. The effect of calcium nanoparticle on immunity was taken into focus in the present study. Wistar rats of either sex of 6 weeks age were divided into two groups of control and treatment and nanocalcium was administered daily for a period of 90 days by oral gavaging. Immunopathological alterations occurred/ encountered due to nanoparticle administration were recorded and the correlation was obtained on calcium nanoparticle being immunotoxic or non immunotoxic. Various parameters of evaluation was involved, Total Leucocyte Count (TLC), Absolute Leucocyte Count (ALC), Serum Globulin, Serum gamma globulin, Lymphocyte Stimulation Test (LST), Macrophage function test (MFT) and Enzyme Linked Immunosorbent Assay (ELISA). The alteration in the level of T-cell and B-cell population was evident of the immunotoxic and cytotoxic effect of calcium nanoparticles. But still much more research into the aspect is needed. Calcium nanoparticles like other metal nanoparticles have resulted in some of the similar results in the present study. As calcium nanoparticles are being used in gene therapy, drug delivery, vaccine adjuvants and many more, henceforth, immunopathological alteration due to calcium nanoparticles might help in knowing the varied aspects of calcium in-vivo.